WHAT IS THE EFFECTS OF PARACETAMOL APPLIED AT DIFFERENT DOSES TO HEAVY METAL LEVELS IN RAT FETUS? - Seher Y., Y.; Vugar A., A.; Adem T., T.; Şükrü , A.; İlyas , U. and Seher , Y. (EurasianUnionScientists, 2020)
Paracetamol is the first preferred pharmacological agent as a pain reliever and antipyretic in all periods of pregnancy. In this study, we aimed to analyze trace element and heavy metal levels in the placenta, intestinal and kidney tissues of rats in the early development period of paracetamol. Sixteen pregnant rats were randomly divided into four groups; the control group, the 50 mg/kg paracetamol group, the 250 mg/kg paracetamol group, the 500 mg/kg paracetamol group. There was a statistically significant decrease in the placental weight of the experimental groups compared to the control group. However, a statistically significant difference was found in terms of cobalt (Co) and lead (Pb) levels compared to the control group and the groups that received various doses of paracetamol. There were also statistically significant differences in intestinal chromium (Cr), selenium (Se) and cadmium (Cd) levels in the studied groups. In addition, significant differences were detected in all trace elements and heavy metal levels except Cd in the groups studied in kidney tissue (p <0.01 for all). As a result, it was determined that the use of paracetamol during pregnancy disrupted the current balance due to the increase in dose. In addition, it was observed that the weight of the placenta decreased due to the paracetamol dose, and the placenta Pb and Co levels increased. In other tissues, there was no toxic concentration at heavy metal and trace element levels, but the highest levels were determined in the control group.